Challenges and Opportunities of Integrating AI in Guidance and Counseling Services for Students in Islamic Higher Education - Ristianti, Dina Hajja; Sofyan, Afriyadi; Aminah, Siti; Muryono, Sigit (Universitas Negeri Padang, 2025)
This study investigates student behavior in utilizing artificial intelligence (AI) to address academic and personal challenges, as well as the subsequent implications for guidance and counseling services within Islamic higher education contexts. A qualitative research approach was employed, utilizing literature reviews and semi-structured interviews conducted with four counselors and six students from an Islamic higher education institution in Bengkulu. Data analysis followed the Miles and Huberman interactive model, encompassing data reduction, data display, and conclusion drawing. The findings indicate that students predominantly use AI tools to efficiently manage academic tasks, such as organizing schedules and accessing information. However, excessive dependence on AI has been observed to adversely affect students' critical thinking abilities, as they often unquestioningly accept instantaneous solutions provided by these technologies without deeper reflection or critical assessment. Additionally, counselors identified significant challenges in integrating AI technologies with a humanistic and spiritually grounded counseling approach rooted in Islamic values, particularly concerning issues of data privacy, confidentiality, and ethical use of technology. The results of this study emphasize the necessity of developing a balanced strategy that combines the advantages of AI with robust human interaction in counseling practices. Consequently, it is recommended that Islamic higher education institutions enhance counselor training in ethical AI utilization, while concurrently supporting students in cultivating critical thinking capacities and moral consciousness aligned with Islamic ethical frameworks. Future research should consider employing quantitative methodologies to statistically assess AI's impact on students' academic and personal development and to broaden the exploration of effective integration between technological advancements and Islamic educational values.